#TITLE_ALTERNATIVE# - ZIVANA (NIM 10205062), ALINE
Magnetic Resonance Imaging (MRI) is a technical drawing based on the principle of the body section magnetic resonance hydrogen atom nucleus. Technical drawing of MRI is relatively complex because the resulting picture depends on many parameters. If the selecting parameters are right, the quality of the image body will be clear, so that the anatomy and pathology body network can be evaluated carefully. This final project is done to study the influence of the value of the TE level image contrast and resolution T2-weight phantom by using spin echo pulse sequence imaging method on the MRI device with 0.5 Tesla in Hasan Sadikin Hospital,Bandung. Imaging uses variations of the value of TE 46.8ms to 360ms, and using a fixed TR of 3500ms with a value parameter imaging T2-weight is fixed too. In T2-weight imaging, this phantom ROI data obtained were presented into the form of a curve T2 relaxation study for each level of explanation as a phantom image contrast. In addition, the level of image resolution is being checked on insert comb on the phantom variations TE value. Results obtained form curve contrast noise ratio (CNR) and graphic profile image phantom T2-weight variation in the value of each TE.